Optimizing the Process of Management of Marine Cargo Insurance Claims at PT. ABC - Ali Imran Ritonga; Kundori Kundori; Karolus G. Sengadji; Hilda Emeraldo Ahmad (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
The purpose of this study is to evaluate how to optimize marine insurance claims as well as the appropriate procedures in the marine cargo insurance claim process and methods in preparing insurance claim documents into accurate and complete documents so that the insurance company that bears all losses is more optimal by the insurance claims. with the details of the calculation of the value of insurance claims that have been insured. This research is divided into three lines of thought, namely identification, and formulation of problems, analysis and discussion, and research results. Identify and formulate problems by identifying possible problems that occur during the claim submission process. Based on the results of this identification then formulate the problem to be discussed in the study. Analysis and discussion by conducting the process of analysis and discussion of the problems that occur through the literature and collecting the necessary data. the next step is a discussion of the problems faced by covering the procedures and stages of filing a claim, the method adopted, and the evaluation method used for optimizing insurance claims. This study uses a qualitative method approach and a descriptive design is used to explain the process, the sample is taken at the shipping company PT. ABC, the representation is expected to be given by this sample. After using descriptive data analysis, the research results obtained that the insurance claim process must pay attention to the person in charge of carrying out marine cargo insurance claims; Types of compensation that can be submitted in the insurance claim process; Requirements in the process of filing an insurance claim, and the evidence that must be prepared to file an insurance claim. In addition, the loss must be filed immediately considering the deadline for submitting an insurance claim. The essence of the claim for ship cargo is compensation paid by the losses borne by the insurer to repair the suffering of the insured from loss of property.